Cover Picture: [FeFe]‐Hydrogenase: Defined Lysate‐Free Maturation Reveals a Key Role for Lipoyl‐H‐Protein in DTMA Ligand Biosynthesis (Angew. Chem. Int. Ed. 22/2022). Issue 22 (8th April 2022) - Pagnier, Adrien; Balci, Batuhan; Shepard, Eric M.; Yang, Hao; Warui, Douglas M.; Impano, Stella; Booker, Squire J.; Hoffman, Brian M.; Broderick, William E.; Broderick, Joan B.
Abstract : The generation of an active [FeFe]‐hydrogenase, the most efficient enzyme for H2 production, requires the synthesis of a complex metal center, the H‐cluster, which is responsible for the reversible reduction of protons to H2. In their Communication (e202203413 ), Joan B. Broderick and co‐workers show that the last step of this synthesis, which consists of the assembly of the azadithiolate bridging molecule, involves the aminomethyl‐lipoyl‐H‐protein from the glycine cleavage system.